MEMBELI DAN MENDIVERSIFIKASIKAN SAHAM: STUDI EMPIRIS PADA 5 BANK TERBESAR DI INDONESIA - Rahmat Budi Santoso; Tri Purwani; Ika Listyawati; Erawati Kartika (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2024)
This study aims to examine the impact of a profitability on its firm value and to analyze the correlation in the stock price movements of the five largest banks in Indonesia. The sample used to determine the impact of profitability on corporate value is based on the financial statements of these companies for the period 2019–2024, resulting in 30 data. The data used to analyze the correlation in stock price movements is based on closing stock prices from January 1, 2019, to October 31, 2024, totaling 1,520 weekly data points and 355 monthly data points. The analysis technique used to examine the impact of profitability on firm value is simple regression analysis, while the correlation in stock price movements of the five largest banks in Indonesia is analyzed using bivariate correlation analysis. The findings indicate that profitability has a positive effect on firm value. However, profitability only slightly explains the corporate value. Furthermore, the correlation between the stock prices of the five largest banks in Indonesia is moderate. The firm value of PT Bank Central Asia Tbk. (BBCA) is higher than the predicted corporate value, indicating that the company is overvalued or too expensive to buy. Additionally, it is not recommended to diversify stocks among these five banks.